2008
DOI: 10.1373/clinchem.2007.095943
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Lactoferrin Concentration and 2 Nonsynonymous LTF Gene Polymorphisms with Dyslipidemia in Men Depends on Glucose-Tolerance Status

Abstract: Background: Lactoferrin, an innate immune protein with antiinflammatory properties, shows considerable antiatherosclerosis activity in animal studies. We investigated the relationship between circulating lactoferrin, lactoferrin gene (LTF, lactotransferrin) polymorphisms, dyslipidemia, and vascular reactivity in the context of glucose-tolerance status in men. Methods: We evaluated 2 nonsynonymous LTF polymorphisms (rs1126477 and rs1126478) and measured circulating lactoferrin concentrations by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 28 publications
2
86
5
2
Order By: Relevance
“…Data and samples from 298 Caucasian men were obtained from population-based prospective studies performed in two regions of Spain between 1996 and 1999: 71 subjects were recruited from the Northwest (Asturias) (20) and 227 from Northeast (Girona) (7). Two hundred and fifty (84%) eligible participants were selected at random from the census and, after a screening visit, they were invited to participate.…”
Section: Patient Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Data and samples from 298 Caucasian men were obtained from population-based prospective studies performed in two regions of Spain between 1996 and 1999: 71 subjects were recruited from the Northwest (Asturias) (20) and 227 from Northeast (Girona) (7). Two hundred and fifty (84%) eligible participants were selected at random from the census and, after a screening visit, they were invited to participate.…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…At 20 min, regular insulin (0.03 U/kg; Actrapid, Novo, Hellerup, Denmark) was injected as a bolus. Additional samples were obtained from a contralateral antecubital vein at times 1, 2, 3, 4, 5,6,7,8,10,12,14,16,19,20,22,23,24,25,27,30,40, 50, 60, 70, 80, 90, 100, 120, 140, 160, and 180 min. Samples were rapidly collected via a three-way stopcock connected to the butterfly needle.…”
Section: Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, bovine LF bLF has been approved as a food additive in Japan while it is included in the generally recognized as safe category in the US. Recently, it was reported that plasma LF levels are inversely correlated with the severity of obesity as well as plasma triglyceride and free fatty acid FA levels in a clinical trial 6 , suggesting that LF may ameliorate lipid metabolism dysfunctions. Several studies have already reported the beneficial effects of bLF on lipid metabolism in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Velliyagounder et al (13) found that a Lys/Arg polymorphism (rs1126478) at position 29 in the N-terminal region of human LTF produced functional differences, and Expression levels of JNK associated with polymorphic lactotransferrin haplotypes in human nasopharyngeal carcinoma that this difference may contribute to the pathogenesis of localized juvenile periodontitis. Similarly, control individuals who were G carriers at rs1126478 had significantly lower fasting triglyceride concentrations and significantly higher high-density lipoprotein cholesterol concentrations than AA homozygotes (14). This evidence suggests that polymorphism of genes may be associated with the expression of other genes.…”
Section: Introductionmentioning
confidence: 88%